Nursing Students’ Perspectives on the Relationship between Virtual Reality Simulation and Clinical Decision-Making, Confidence, and Anxiety: A Cross-Sectional Study - HAZEM ALFANASH; MAHMOUD AL-KALALDEH; KHALDOON ALNAWAFLEH; WESAM ALMAGHARBEH (Journal of Advances in Medical Education and Professionalism)
Introduction: This study addresses this gap by assessing the relationship of VR simulation with improving clinical decisionmaking, confidence, and anxiety reduction among nursing students. The aim of this study is the relationship between virtual reality simulation and their clinical decision-making, confidence, and anxiety reduction using a cross-sectional study from the perspectives of nursing students.Methods: This cross-sectional study surveyed 200 nursing students enrolled in clinical courses utilizing virtual reality (VR) simulation for educational purposes. A structured questionnairewas used to assess their clinical decision-making, confidence, and anxiety reduction following the VR simulation course. The survey included scales validated through a panel of experts andquestionnaire validation methodologies, using a 5-point Likert scale. Descriptive statistics were used to summarize the data, and inferential statistical tests, including Pearson’s correlation and independent-sample t-tests, were conducted to examine the associations. Multiple linear regression analysis was performed to assess the predictive value of confidence and anxiety on clinical decision-making while controlling demographic variables.Results: A total of 200 nursing students participated in the study. The mean (SD) clinical decision-making score was 3.16 (1.23) out of 5, while confidence and anxiety reduction scores were 2.64 (1.34) and 2.49 (1.32), respectively. No significant correlation was found between decision-making and confidence (r=-0.079, p=0.264) or anxiety scores (r=0.121, p=0.088), but confidence and anxiety scores showed a weak direct correlation (r=0.180, p=0.011). Multiple linear regression analysis revealed that confidence and anxiety were not significant predictors of decision-making, but gender was a significant predictor, with males scoring higher (β=0.19, p=0.041).Conclusions: While VR directly influences decision-making, it has a limited association with changes in nursing students’ confidence and anxiety levels. These findings suggest that VRsimulation alone may not be sufficient for enhancing confidence and reducing anxiety and should be integrated with other instructional strategies to maximize its effectiveness in nursing education. Future studies should explore complementary training methods to improve clinical preparedness.